Corals in a Changing World 2018
DOI: 10.5772/intechopen.74686
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationship (SAR) Studies to Maximize the Activity of Compounds Isolated from Octocorals

Abstract: This chapter presents some significant study cases on octocoral organisms (Eunicea succinea, Eunicea mammosa, Eunicea knighti, Pseudoplexaura flagellosa, Eunicea laciniata, Antillogorgia elisabethae, Muricea austera, Paragorgia sp., Lobophyton sp., Sarcophyton glaucum and Sinularia lochmodes) that have been identified as a source of promising bioactive compounds and whose results have further been used for studies on structure-activity relationship (SAR) as a strategy to increase the value of the activity init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…It has become increasingly essential as a tool for organizing, mining, and interpreting data, to guide further investigation for drug discovery [ 154 ]. It is also a strategy to increase the value of the activity initially detected [ 155 ]. Natural products contain steric and electronic features in their bioactive sites (pharmacophores), which are responsible for the optimal supramolecular interactions with specific biologic targets and to trigger (or block) their biologic responses.…”
Section: Structure–activity Relationships Of Some Promising Natural P...mentioning
confidence: 99%
“…It has become increasingly essential as a tool for organizing, mining, and interpreting data, to guide further investigation for drug discovery [ 154 ]. It is also a strategy to increase the value of the activity initially detected [ 155 ]. Natural products contain steric and electronic features in their bioactive sites (pharmacophores), which are responsible for the optimal supramolecular interactions with specific biologic targets and to trigger (or block) their biologic responses.…”
Section: Structure–activity Relationships Of Some Promising Natural P...mentioning
confidence: 99%
“…However, due to the structural differences between Pseudopterosin compounds (glycosylation position, aglycone stereochemistry, and carbon skeleton) as well as differences in disease pathology and pathophysiology, no conclusive comparison of relative potency can be made. [24][25][26][27][28]38 Furthermore, it has been demonstrated that PsG, PsP, PsQ, PsS, PsT, PsU, 3-O-acetyl-PsU, seco-PsJ and seco-PsK are not selectively cytotoxic to malignant cell lines as they exhibited similar cytotoxic effects in the non-malignant cell line. 25 In regard to PsH, additional studies will need to be conducted on non-malignant cell lines to determine if PsH is selectively cytotoxic to PC-3 cells.…”
Section: Pseudopterosin H Reduces Pc-3 Cell Viability By Inducing Apo...mentioning
confidence: 99%
“…[23][24][25] Pseudopterosins are isolated from gorgonian soft corals and each derivative possess a tricyclic diterpene core with a fucose or xylose moiety and differ in the degree of acetylation of the glycoside group as well as stereochemistry (C1 position can be alpha or beta). 23,26 These compounds are of interest for therapeutic use in various human diseases due to their diverse range of biological activities that include anti-inflammatory, analgesic, anti-microbial, anti-proliferative, wound healing, neuroprotective, and anti-cancer effects. 25,[27][28][29][30] The known anti-inflammatory properties of Pseudopterosin compounds (hypothesized to occur via blocking the inflammatory pathway nuclear factor κB (NF-κB) through novel mechanisms of action), have resulted in their use in cosmetic skin care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations